Research status and trends of enterprise safety culture: a knowledge graph analysis based on CiteSpace - Wen, Ming; Gou, Zhaohui; Xiong, Chaogang; Wang, Yao; Cheng, Dan (Frontiers in Public Health, 2024)
The cultivation of safety culture within enterprises has evolved into a pivotal facet of overall safety progress, drawing increased attention from a myriad of businesses. With a comprehensive examination of relevant literature, 635 documents from both domestic and international sources were selected as the subjects of analysis. The developmental trends, both domestically and internationally, follow a generally consistent pattern, resembling an inverted “V” shape. The initial phase witnessed gradual development, followed by a substantial and rapid growth phase in the mid-term. In the later phase, a decline is observed. This study utilizes the CiteSpace software for keyword clustering analysis, employing the Log Likelihood Ratio (LLR) algorithm with default parameters to delve into the themes within the specific research field of enterprise safety culture. It was observed that domestic research predominantly centers on the practical perspective of mitigating accidents through the establishment of enterprise safety culture, while international research places greater emphasis on theoretical considerations, specifically focusing on the impact of safety culture atmospheres within enterprises on employees.